2010
DOI: 10.1186/1471-2229-10-223
|View full text |Cite
|
Sign up to set email alerts
|

The physical and functional borders of transit peptide-like sequences in secondary endosymbionts

Abstract: BackgroundPlastids rely on protein supply by their host cells. In plastids surrounded by two membranes (primary plastids) targeting of these proteins is facilitated by an N-terminal targeting signal, the transit peptide. In secondary plastids (surrounded by three or four membranes), transit peptide-like regions are an essential part of a bipartite topogenic signal sequence (BTS), and generally found adjacent to a N-terminally located signal peptide of the plastid pre-proteins. As in primary plastids, for which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 42 publications
2
18
0
Order By: Relevance
“…Diatom TPs may not need to be as long as plant TPs because they are hidden until the SP is cleaved off after the protein is already partly inserted into the ER, avoiding the danger of misdirection to the mitochondrion. The previously reported net positive charge, which was confirmed for almost all TPs identified in our study, is thought to be required for transit across the plastid envelope, but not for traversing the periplastidal membrane [36]. The TPs were enriched in hydroxylated amino acids that may play a role in keeping the precursor in an import competent state in the periplasm, possibly by interaction with resident chaperones [37,38].…”
Section: Discussionsupporting
confidence: 83%
“…Diatom TPs may not need to be as long as plant TPs because they are hidden until the SP is cleaved off after the protein is already partly inserted into the ER, avoiding the danger of misdirection to the mitochondrion. The previously reported net positive charge, which was confirmed for almost all TPs identified in our study, is thought to be required for transit across the plastid envelope, but not for traversing the periplastidal membrane [36]. The TPs were enriched in hydroxylated amino acids that may play a role in keeping the precursor in an import competent state in the periplasm, possibly by interaction with resident chaperones [37,38].…”
Section: Discussionsupporting
confidence: 83%
“…Earlier studies have revealed that the presence of a GFP reporter directly adjacent to potential trafficking motifs may either inhibit or be conducive to protein transport2021. We wished to investigate whether the GFP reporter itself may be acting as a spacer which may either increase or decrease export efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…However, in diatoms intermediates that are transported across only one or two of the four plastid membranes can be discriminated from those imported across all four, and studies in the model system Phaeodactylum tricornutum revealed a complex set of signals [43]. It was shown that the positive net charge of the TP is important to cross the two innermost membranes, and required to cross the second outermost membrane into the PPC [44]. Negative charges in the TP were shown to inhibit entry into the PPC of diatoms [44], but in contrast are required for PPC targeting in chlorarachniophytes [45].…”
Section: Signals For Organellar Targetingmentioning
confidence: 99%
“…It was shown that the positive net charge of the TP is important to cross the two innermost membranes, and required to cross the second outermost membrane into the PPC [44]. Negative charges in the TP were shown to inhibit entry into the PPC of diatoms [44], but in contrast are required for PPC targeting in chlorarachniophytes [45]. This may represent a fundamental difference in these pathways originating from different algal lineages.…”
Section: Signals For Organellar Targetingmentioning
confidence: 99%
See 1 more Smart Citation